Molecular Dynamics Simulation Of Pdms Nanostructure Distortion In Soft Lithography Demolding Process - Manap, Abdul Haadi Abdul (2021)
In this thesis, the distortion of PDMS nanostructures in the demolding process of the soft lithography process was studied and investigated using the computational method. Nanoimprint lithography uses the simple concept of material displacement by mechanical contact. While the idea is simple, many factors may distort the replications, such as temperature, pressure, aspect ratio and peeling-off technique. Thus, when all distortion factors are accumulated, it is crucial in the manufacturing process to understand the stress and strain relationship of materials in the demolding process. Although there are extensive studies and research conducted to optimize the fabrication process, most of them are experimental focusing on the process outcome and parameter optimization rather than the fundamental study of the process. In this thesis, the molecular dynamics simulation method was utilized to fill the gap to breach the fundamental analysis and the process outcome .Two forces fields have been used to study the distortions of nanostructures in the demolding process. The force fields are Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies (COMPASS) and Polymer Consistent Forcefield (PCFF). The results from these force fields will be utilized to find the nanostructures' stress-strain relationship when forces were applied. This thesis will investigate two types of nanostructures which are nanocones and nanopillar. The results from the simulation will be analyzed and compared with experimental results. This thesis's main interest is to find the stress and strain relationship of the nanostructure and relate it to molecular mechanics. The experimental results show clear signs of elongation during demolding. After the peeling process, PDMS nanopillars became 10–60% longer in height than the mold size, and PDMS nanocones replica yields 150 % - 160 % larger in height compared to the mold size dimensions right before rupture. The experiment's observation gives the direction for this study to investigate the distortion of PDMS nanostructures in the demolding soft lithography process using molecular dynamics simulation. MD simulations found that PDMS nanocones at temperatures T=300 K, 310 K and 320 K under uniaxial tensile stress show the characteristic of flexible plastic with noticeable yielding. The Ultimate Tensile Stress for PDMS nanocones ranges between 4.335 MPa - 6.478 MPa. MD simulations demonstrate that the PDMS nanopillar using 8 series and 12 series monomer under tensile stress also shows characteristics of flexible plastic with significant yielding. The PDMS nanopillar has a lower Young’s Modulus, which are around 67–71 % of the bulk value. The Ultimate Tensile Stress for PDMS nanopillar is also about 46.3 % of the bulk value, and Poisson’s Ratio is about 48.0 % compared to the bulk value.